Enhanced Human Immunodeficiency Virus Type 1 Expression and Neuropathogenesis in Knockout Mice Lacking Type I Interferon Responses. Issue 1 (January 2014) - He, Hongxia; Sharer, Leroy R.; Chao, Wei; Gu, Chao-Jiang; Borjabad, Alejandra; Hadas, Eran; Kelschenbach, Jennifer; Ichiyama, Koji; Do, Meilan; Potash, Mary Jane; Volsky, David J.
Abstract: The roles of Type I interferon (IFN) in human immunodeficiency virus Type 1 (HIV-1) neuropathogenesis are poorly understood; both protective and deleterious effects of IFN signaling have been described. We used genetically modified mice deficient in the Type I IFN receptor (IFNRKO) to analyze the progress of HIV-1 brain infection and neuropathogenesis in the absence of IFN signaling. IFNRKO and wild-type (WT) mice on the 129xSv/Ev or C57BL/6 strain backgrounds were infected systemically with EcoHIV, a chimeric HIV-1 that productively infects mice. IFNRKO mice showed higher HIV-1 expression in spleen and peritoneal macrophages and greater virus infiltration into the brain compared to WT mice. Neuropathogenesis was studied by histopathological, immunohisto-chemical, immunofluorescence, and polymerase chain reaction analyses of brain tissues after the virus was inoculated into the brain by stereotaxic intracerebral injection. Both IFNRKO and WT mice showed readily detectable HIV-1 and brain lesions, including microglial activation, astrocytosis, and increased expression of genes coding for inflammatory cytokines and chemokines typical of human HIV-1 brain disease. Parameters of HIV-1 neuropathogenesis, including HIV-1 expression in microglia/macrophages, were significantly greater in IFNRKO than in WT mice. Our results show unequivocally that Type I IFN signaling and responses limit HIV-1 infection and pathogenesis in the brains of mice.